Activated carbon spheres (ACS)@SnO2@NiO with a 3D nanospherical structure and its synergistic effect with AHP on improving the flame retardancy of epoxy resin. (13th January 2019) - Liu, Hao; Wu, Weihong; He, Shaorui; Song, Qingyi; Li, Weihao; Zhang, Jingyi; Qu, Hongqiang; Xu, Jianzhong
Abstract : A novel activated carbon spheres (ACS)@SnO2 @NiO hierarchical hybrid architecture was first synthesized and applied for enhancing the flame retardancy of epoxy (EP) resin via a cooperative effect. Herein, using activated carbon microspheres as the template, SnO2 and NiO nanospheres were successively anchored to it by a sedimentation‐calcination strategy. The well‐designed ACS@SnO2 @NiO significantly enhanced the flame retardancy for consistency of EP composites, as demonstrated by thermogravimetric and cone calorimeter experiments. For instance, the incorporation of 2 wt% ACS@SnO2@NiO decreased by 15.5% maximum in the total smoke production, accompanying the higher graphitized char layer. In addition, the synergetic mechanism of flame retardancy between ACS@SnO2 @NiO and aluminum hypophosphite (AHP) was investigated. The obtained sample satisfied the UL‐94 V‐0 rating with a 5.0 wt% addition of AHP and ACS@SnO2 @NiO (the ratio of the mass fraction of AHP to ACS@SnO2 @NiO is 4.5:0.5). Notably, the incorporation of AHP and ACS@SnO2 @NiO resulted in a significant decrease in the fire hazard properties of EP resin; for instance, 4.5AHP‐0.5ACS@SnO2 @NiO/EP resulted in a maximum decrease of 32.4% in the total smoke production as compared with that of pure EP resin. It should be noted that the improved flame‐retardant performance for the EP composites is primarily attributed to the synergistic effect of ACS@SnO2 @NiO and AHP in promoting the formation of residual char in the condensed phase.